Contributing Factors to Apple’s Sustainability in Malaysia’s Information and Communication Technology Industry - Edeh, Friday Ogbu; Teoh, Kok Ban; Murugan, Yashene; Kee, Daisy Mui Hung; Wong, Joey; Wong, Xin Shi; Maheswaran, Yashwiny; Jacinta, Ofojama Blessing (AIBPM Publisher, 2021)
Apple has a large customer base in Malaysia because they offer products of superior design and features. The main objective of this study is to determine the contributing factors to Apple’s sustainability in Malaysia’s Information and Communication Technology (ICT) Industry. This study is conducted based on quantitative research with 100 targeted respondents from Malaysia. The findings indicate that the marketing strategies, brand awareness, and customer experience are the major factors of the successful pathway of Apple’s sustainability. The research concludes that Apple Industry should adapt a frequent reengineering approach where the existing and upcoming Apple products will satisfy customer needs.